Performance of composite cones under axial compression loading - Khalid, Asad Abdullah; Sahari, B.B; Khalid, Y.A (Elsevier, 2002)
Experimental and finite-element axial compression analyses for cotton/epoxy and glass/epoxy composite cones have been carried out. Quasi-static axial crushing was used for fiber orientation angles of 90 and 80° with semi-vertex angles of 5, 10 and 20°. Six initial cone diameters were selected. Four layers of glass/epoxy and eight layers of cotton/epoxy were fabricated by a filament winding process. The load/displacement response was plotted and the energy absorption values were calculated for all composite cones tested. A finite-element analysis for cones of the same dimensions and materials was also done. Results from this investigation show that the load required and the specific energy absorption for glass/epoxy cones were higher than those for cotton/epoxy cones for all the cases studied. It has been found that there is a slight increase in the load capability and the energy absorption when using fabricated composite cones of 80° fiber orientation angle instead of 90° for both of cotton-and glass/epoxy cones. It has also been observed that with increasing cone angle from 5 to 20° for all the tested specimens, composite cones can withstand higher loads and the specific energy absorption was improved. The percentage increase in load capacity for cotton/epoxy cones varies between 27.5 and 35.2% and for glass/epoxy cones 37 and 42.4%. The specific energy absorption was in the range of 8.6-13.3% for cotton fiber/epoxy cones and 12.6-24.2 for glass/epoxy cones. The load-displacement difference between the experimental and finite element results fell in the 1.7-14.4% range.